Application of the theory of planned behavior in the design and implementation of a behavior-based safety plan in the workplace - Masoud Motalebi Gh; Zahra Rahimi Khalifeh Kandi; Sajjad Rostamzadeh; Aliasghar Farshad (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Many accidents in industries occur due to unsafe practices and unsafe conditions. Occupational accidents endanger the health of workers and impose excessive costs on the employers. This study was designed and conducted to evaluate and implement a behavior-based safety approach in an industrial workplace based on the theory of planned behavior. MATERIALS AND METHODS: The present study was a quasi-experimental study performed on 90 supervisors of an industrial workplace. Behavior-based safety interventions were performed based on the components of the theory of planned behavior using nine strategies of health education and health promotion, including skills training, participation, and social support. The data collection tool consisted of a researcher-made questionnaire that was answered by the supervisors before and 6 months after the intervention. The collected data were evaluated using SPSS 22 software. The significance level was considered 0.05. RESULTS: The results showed that the constructs of subjective norms, attitude, and perceived control of behavior predict the safe behavior of supervisors. After behavior-based safety interventions, significant changes were observed in subjective norms, intention, attitude, and perceived control of behavior (P < 0.001) compared to before the intervention. CONCLUSION: The results of this study showed the improvement of safe behavior of supervisors in the workplace due to behavioral-based safety interventions using the theory of planned behavior. Accordingly, this theory can be used as a suitable theoretical framework for designing and implementing interventions to promote safe behaviors of employees in the workplace.